Enterprise and Small Business: Principles, Practice and Policy - Sara Carter; Dylan Jones-Evans (UK Pearson, 2012)
This text delivers the latest research, current thinking and practice, and looks at future trends, as well as covering hot topics such as e-commerce, leadership and venture capital. This highly successful book provides a comprehensive introduction to entrepreneurship, enterprise and small business for the undergraduate and postgraduate student. With over 30 specialist contributors from academic institutions in the UK, Europe and the USA, this second edition while building on the foundations of the first has been extensively revised and updated.Key features: * Twenty-four chapters covering the most essential and contemporary topics taught on small business and enterprise courses * Contributions from leading international academics, each a subject specialist in the field * Strong theoretical and research pedigree ensures high degree of academic credibility * Encourages critical thinking through challenging discussion questions * Provides students with a guide to further study and weblinks Enterprise and Small Business is ideal for students taking courses in entrepreneurship and small business management at undergraduate and post-graduate level. Sara Carter is Professor of Entrepreneurship in the Department of Management and Organization, University of Stirling, UK. Dylan Jones-Evans is Adjunct Professor of Entrepreneurship at the Turku School of Economics and Business Administration in Finland, and Director of the National Entrepreneurship Observatory at Cardiff University, UK.
Age Group: Adult
Keywords: Business; Business enterprises; Enterprises; Textbooks; Enterprise and Practice (BIN2045-N)